1085 Equestrian Related Pelvic and Acetabular Fractures – Experience from a Major Trauma Centre in England. (12th October 2021) - Hussain, A; Ghobrial, M; Davies, B; Hull, P; Carrothers, A; Rawal, J; Chou, D
Abstract: Introduction: Equestrianism is enjoyed by three million people in the UK; however, there is a lack of literature on pelvic and acetabular (P&A) injuries incurred through the sport. We aim to describe P&A injuries sustained in equestrian accidents, discuss management, and establish their outcomes. Method: Data was extracted from a prospectively collected database of referrals to the P&A Service of a Major Trauma Centre (MTC) from 01/01/2016 to 31/12/2020 and cross-referenced with medical records. Results: 60 of the 1, 218 P&A referrals were secondary to horse-riding accidents. Mean age 45 (SD 16.59); 46 female; 33 managed non-operatively and 27 managed operatively at the MTC. There was sufficient information for 59 cases to be classified; 46 of the injuries were pelvic fractures (10 anterior-posterior compression; 29 lateral compression; 4 sacral and 3 pubic rami fractures) and 13 were acetabular (2 anterior column; 1 anterior wall; 2 associated both columns; 1 posterior column and posterior wall; 1 posterior wall; 2 T-shaped and 4 transverse fractures). The operative group were managed by examination under anaesthesia (n = 3), open reduction internal fixation (n = 22) or percutaneous fixation (n = 2). Mean hospitalisation was 9.2 days (SD 5.44). 81% were non-weight-bearing post-operatively and mean time to independent mobilisation was 12.6 weeks (SD 7.09). Return-to-riding information was available for 8 patients with a mean of 29.5 weeks (SD 11.55). Conclusions: Equestrianism can result in significant P&A injuries. Patients should be counselled that they may have a long recovery, a protracted return-to-riding time and some may never return to the sport.